2022
DOI: 10.4103/1673-5374.332203
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intraspinal pressure in traumatic spinal cord injury is a promising therapeutic target

Abstract: The currently recommended management for acute traumatic spinal cord injury aims to reduce the incidence of secondary injury and promote functional recovery. Elevated intraspinal pressure (ISP) likely plays an important role in the processes involved in secondary spinal cord injury, and should not be overlooked. However, the factors and detailed time course contributing to elevated ISP and its impact on pathophysiology after traumatic spinal cord injury have not been reviewed in the literature. Here, we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 109 publications
0
22
0
Order By: Relevance
“…Timely decompression can prevent and reduce secondary injury. The earlier the surgical decompression, the better the prognosis of patients with spinal cord injury [ 19 – 22 ]. (3) Transportation and protection before admission: the spinal cord without protection from the spinal column may be compressed and stretched if no proper protection is given during the transportation to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Timely decompression can prevent and reduce secondary injury. The earlier the surgical decompression, the better the prognosis of patients with spinal cord injury [ 19 – 22 ]. (3) Transportation and protection before admission: the spinal cord without protection from the spinal column may be compressed and stretched if no proper protection is given during the transportation to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This notable neurological recovery is consistent with previous studies. This result might be explained by early surgical decompression expeditiously relieving mechanical spinal cord compression, thereby improving the spinal cord blood supply to avoid or mitigate secondary damage cascades and SCHS and to facilitate the restoration of spinal cord function (2,22,29). Badhiwala and colleagues stated that "time is spine" (30) and highlighted that there is a critical time window after primary injury to the spinal cord during which secondary injury mechanisms, which cause further neural tissue destruction, may be curtailed (31).…”
Section: Discussionmentioning
confidence: 99%
“…The higher odds of achieving an improvement in the AIS grade of at least a one grade in our study than in Jug's study might be due to the difference in the surgical method used for decompression; extensive posterior laminoplasty (assisted with posterior pedicle screw fixation if necessary) was performed in our study, whereas anterior discectomy (ADF) or corpectomy (ACF) and fusion was preferred in Jug's study. Obviously, more adequate decompression increases the possibility of upward AIS grade conversion (2,7,18). In a recent study, Piazza reported that posterior cervical laminectomy results in better radiological decompression of the posterior CSF space than does ADF (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it relevant to study the different and interconnected mechanisms underlying spinal edema. However, the contusion model requires laminectomy to access to the spinal tissue unlike other models used to study ISP in closed canals [ 87 , 88 ]. This inherent step of the surgery by itself alleviates the impact of edema and the subsequent pressure increase, as reported in clinical findings [ 89 , 90 , 91 ].…”
Section: Edema Formation After Sci: a Loop Of Interconnected Mechanismsmentioning
confidence: 99%